2013
DOI: 10.1007/s00726-013-1558-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of l-arginine-nitric oxide pathway in bacterial translocation

Abstract: This study investigated the nitric oxide (NO) role as a mediator of arginine on bacterial translocation (BT) and gut damage in mice after intestinal obstruction (IO). The effects of pretreatment with arginine with or without NO inhibition on the systemic and local immunological response were also assessed. Mice were categorized into four groups. Group ARG received chow containing 2 % arginine, while group ARG + L-NAME received the same diet plus L-NAME (N-nitro-L-arginine methyl ester) by gavage. The IO and Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…However, the ratio of TNF‐α/IL‐10 was significantly lower in the WT arginine‐supplemented animals. These results are similar to findings from other in vitro and in vivo studies illustrating the immunomodulatory role of arginine 7 , 22 , 23 . A study also conducted by our group 24 showed that supplementation of citrulline, an amino acid precursor to arginine, maintained the levels of IL‐10 and reduced serum IFN‐γ levels in a similar animal model of IO.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the ratio of TNF‐α/IL‐10 was significantly lower in the WT arginine‐supplemented animals. These results are similar to findings from other in vitro and in vivo studies illustrating the immunomodulatory role of arginine 7 , 22 , 23 . A study also conducted by our group 24 showed that supplementation of citrulline, an amino acid precursor to arginine, maintained the levels of IL‐10 and reduced serum IFN‐γ levels in a similar animal model of IO.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, in the Arg WT group, the cell media concentration of TNF‐α was significantly reduced, and this may be related to the NO derivative of arginine, which seems to suppress the production of proinflammatory cytokines by macrophages in the spleen. This may explain our previous results on the positive impact of arginine supplementation on bacterial translocation and intestinal permeability, 4 7 since continuous production of proinflammatory cytokines, such as TNF‐α may be more deleterious than beneficial during acute stress conditions 19 , 20 . Corroborating these data, Eun et al 20 evaluated the immunomodulatory effect of NO and observed that NO synthesis reduced the synthesis of the proinflammatory cytokines IL‐2 and IFN‐γ in cultured splenocytes.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Studies have demonstrated that arginine supplementation improves various clinical parameters, 6 , 10 increases claudin‐1 expression, 10 and decreases colonic permeability and inflammatory cell infiltration 6 in experimental models of colitis. Previous results obtained by our research group have shown that arginine protects the intestinal mucosa, reducing intestinal permeability and bacterial translocation in experimental intestinal obstruction models 11 14 as well as in a mouse model of physical exercise under heat stress 15 …”
Section: Introductionmentioning
confidence: 92%
“…This fourth phase is characterized by integrity loss of mucosal and tissue morphological changes [7][8][9]. Reduction of the villus' height in humans [16] and animals [11] were observed after chemotherapy treatment. Due to epithelium ulceration the intestinal barrier becomes weak, which could lead to BT increasing the risk of bacteremia and sepsis [7][8][9].…”
Section: Introductionmentioning
confidence: 99%